Tantangan dan Strategi Guru dalam Implementasi Kurikulum Merdeka Belajar di Sekolah Dasar - Ahmad Ahmad (Journal of Humanities, Social Sciences, and Education, 2025)
The Merdeka Belajar Curriculum is one of the initiatives of the Indonesian Ministry of Education, Culture, Research, and Technology to provide more freedom and autonomy to educational units and teachers in the learning process. However, its implementation in Elementary Schools (SD) presents various complex challenges, especially in terms of teacher readiness, availability of facilities, and understanding of the essence of the curriculum itself. This literature study aims to identify the various challenges faced by elementary school teachers in implementing the Merdeka Belajar Curriculum and summarize the strategies that have been implemented to overcome them. This study uses a qualitative method with a literature study approach from various current academic sources, both relevant national and international journals. The results of the study show that the main challenges lie in the aspects of teacher competence, adaptation to digital technology, differentiated learning planning, and strengthening formative assessments. The strategies that emerge include ongoing training, strengthening teacher learning communities, collaboration between stakeholders, and the preparation of flexible and contextual teaching tools. This study concludes that the success of the Merdeka Belajar Curriculum implementation is highly dependent on the synergy between teachers, principals, education offices, and central policies. Systematic and sustainable support is needed to improve teacher capacity in carrying out meaningful educational transformation